1994
DOI: 10.1139/v94-083
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance study of the reaction of hydrogen atoms with methane

Abstract: . Can. J. Chem. 72,600 (1994).The reaction: H + CH, + CH3 + Hz has been investigated in a flow system between 348 and 421 K. Hydrogen atoms were generated in a microwave discharge, introduced to the reactor through a movable injector, and monitored by electron spin resonance. After an initial decay attributed to reaction with impurity, the hydrogen atom concentration decayed in a pseudo-first-order manner. Ethane was detected by gas chromatography, consistent with its formation by the following reaction: 2CH3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 13 publications
5
29
1
Order By: Relevance
“…Because Sutherland et al based their recommendation in the low-temperature regime on the most recent experimental data obtained by Marquire et al (36), this difference results from the difference between the present calculations and the experiments of Marquire et al…”
contrasting
confidence: 55%
“…Because Sutherland et al based their recommendation in the low-temperature regime on the most recent experimental data obtained by Marquire et al (36), this difference results from the difference between the present calculations and the experiments of Marquire et al…”
contrasting
confidence: 55%
“…It has therefore been widely studied both experimentally [18][19][20][21][22][23] and theoretically. 9,10,24-39 Two-dimensional quantum scattering calculations on this system have shown a strong dependence of the thermal rate constants on the choice of coordinates for the spectator modes.…”
Section: Introductionmentioning
confidence: 99%
“…Early work includes two studies by Bauer and coworkers [5,9] and four more noteworthy studies have been reported recently [11][12][13][14]. The reverse of reaction (1),…”
Section: Introductionmentioning
confidence: 99%